Alterations in uterine hemodynamics caused by uterine fibroids and their impact on in vitro fertilization outcomes - Moon, Jei-Won (Clin Exp Reprod Med, 2015)
OBJECTIVE: To investigate the impact of fibroids on the blood flow of the uterine and subendometrial arteries and in vitro fertilization (IVF) outcomes. METHODS: In this study, we analyzed 86 IVF/intracytoplasmic sperm injection (ICSI) cycles in which a gonadotropin-releasing hormone antagonist protocol was used for controlled ovarian stimulation between January 2008 and March 2009. The subjects comprised 86 infertile women with (fibroid group, n=43) or without (control group, n=43) uterine fibroids. RESULTS: Patient characteristics were similar between the fibroid and control groups. The IVF/ICSI outcomes in patients with fibroids were similar to those of patients in the control group. The resistance index (RI) and pulsatile index (PI) of the uterine and subendometrial arteries on the day of embryo transfer were also comparable between the two groups. IVF outcomes and uterine hemodynamics in patients with multiple (≥2) fibroids were similar to those of patients with a single fibroid. However, clinical pregnancy and implantation rates were significantly lower in patients with fibroids who experienced uterine cavity distortion than in patients with fibroids who had a normal uterine cavity (both p<0.05). The RI and PI of the subendometrial artery were significantly higher on the day of embryo transfer in patients with fibroids who experienced uterine cavity distortion than in patients with fibroids who had a normal uterine cavity (both p<0.05). CONCLUSION: Fibroids which distorting the uterine cavity might impair the subendometrial artery blood flow clinical pregnancy rate and embryo implantation rate in infertile patients undergoing IVF. Otherwise, IVF outcomes were not influenced by the presence of uterine fibroids.